Use of complementary and alternative medicine among osteoarthritic patients: a review - Khan, Muhammad Umair; Jamshed, Shazia; Akram, Ahmad; Mohd Ashraf, Ahmad Bidin; Siddiqui, Mohammad Jamshed Ahmad; Al-Shami, Abdul Kareem (JCDR Research and Publications (P) Limited, 2016)
INTRODUCTION: One of the most important indications of complementary and alternative medicines (CAM) is in arthritis. The popularity of CAM in arthritis is consistently on the rise because of the potential side effects of the conventional therapy (Methotrexate) of arthritis. In view of this, it was important to summarize the information, for healthcare professionals and the patients, about the safety and effectiveness of various CAM use in arthritis.